O14 Benefit of thrombectomy in patients with extensive baseline stroke depends on early ischemic lesion water uptake: results from the I-LAST study. (29th August 2022) - Broocks, G; Meyer, L; Hanning, U; Faizy, T; Fiehler, J; Kemmling, A
Abstract : Background: The benefit of mechanical thrombectomy (MT) in ischemic stroke patients with ASPECTS<6 is still uncertain. ASPECTS rating is based on the presence of relative hypoattenuation, however the degree of hypoattenuation, which directly reflects net uptake of water, is currently not considered as imaging biomarker in stroke triage. We hypothesized that quantitative lesion water uptake in admission-CT mediates the effect of thrombectomy on functional outcome in low ASPECTS patients. Methods: For this multicenter study, anterior circulation stroke patients with ASPECTS≤5 were consecutively analyzed. Net water uptake (NWU) was assessed as quantitative imaging biomarker in admission-CT. Primary endpoint was favorable functional outcome defined as mRS≤3 at day 90. The effect of recanalization on functional outcome was analyzed according to the degree of NWU within the early infarct lesion. Results: 254 patients were included, of which 148 (58%) underwent MT. The rate of favorable outcome was 27.6% in patients with low NWU (<11.4%) versus 6.3% in patients with high NWU (≥11.4%;p<0.0001). NWU was an independent predictor of outcome, while vessel recanalization (mTICI≥2b) was only associated with better outcomes if NWU was lower than 12.6%. In inverse-probability-weighting analysis, recanalization was associated with 20.7% (p=0.01) increase in favorable outcome in patients with low NWU compared to 9.1% (p=0.06) in patients with high NWU. Discussion: Early NWU was an independent predictor of clinical outcome, and might serve as an indicator of futile MT in low ASPECTS patients. NWU could be tested as tool to select low ASPECTS patients for MT. References: Sarraj A, Hassan AE, Savitz S, et al . Outcomes of Endovascular Thrombectomy vs Medical Management Alone in Patients with Large Ischemic Cores: A Secondary Analysis of the Optimizing Patient's Selection for Endovascular Treatment in Acute Ischemic Stroke (Select) Study. Jama Neurol 2019. Mcdonough R, Elsayed S, Faizy TD, et al . Computed Tomography-based Triage of Extensive Baseline Infarction: Aspects and Collaterals versus Perfusion Imaging for Outcome Prediction. J Neurointerv Surg 2020. Broocks G, Kniep H, Schramm P, et al . Patients with Low Alberta Stroke Program Early CT Score (Aspects) but Good Collaterals Benefit from Endovascular Recanalization. J Neurointerv Surg 2020;12:747–752. Do you have any conflict of interest to declare? : No